ERADICATION OF CRIMINAL ACTS OF TERRORISM AND PROTECTION OF HUMAN RIGHTS IN INDONESIA - Parlindungan Purba; Rolando Marpaung; Micael Jeriko Damanik; Hendrik Wahyu (PT. Radja Intercontinental Publishing, 2023)
The Law on the Eradication of Terrorism Crime certainly implies the existence of coercive actions by the state against individuals or groups that commit acts of terror in Indonesia. There are allegations of actions that have the potential to violate Human Rights in the process of arrest and detention of individuals suspected of being terrorists. The intended action was allegedly carried out by law enforcement officers, especially in the practice of implementing Article 28 of the Law referred to in terms of regulating arrests and detentions that were not yet in line with respect and protection of human rights. This research is a descriptive analytical study that wants to describe what is legitimate or not a regulatory restriction of human rights, in the paradigm of